Geographic Information System (GIS) In Mapping of Mine Suspected Area in the Republic of Serpska (Global Journal of Science Frontier Research, 2015)
Geographic Information System (GIS) is a computing system to capture, store, manipulate, analyze, manage, and represent all types of geographical data. GIS systems are used in cartography, so that the simplest explanation of GIS was merging of cartography and database. There is almost no human activity related to a geographical territory, and the whole planet, which could not be improved by using an optimized GIS system. GIS allows efficient prediction and managing of resources to protect the environment. GIS technology provides public safety and the ability to manage and analyze large amounts of information. In the Republic of Srpska, as well as the whole country there are still a large number of mines from the Civil War (1992)(1993)(1994)(1995). This paper describes the application of GIS and mapping the mine suspected areas, and the ability to facilitate consideration of the surface displacement due to severe flooding which occurred in the Republic of Serbian and region on May 2014, taking into account that the largest concentration of mines from the war was just through the length of the flooded river, which is the risk and responsibility to the Republic of Serbian and the states that border.
Keywords: GIS; environmental protection; mine suspected area; flood in